2022
DOI: 10.1172/jci.insight.148586
|View full text |Cite
|
Sign up to set email alerts
|

The timing of auditory sensory deficits in Norrie disease has implications for therapeutic intervention

Abstract: Norrie disease is caused by mutation of the NDP gene, presenting as congenital blindness followed by later onset of hearing loss. Protecting patients from hearing loss is critical for maintaining their quality of life. This study aimed to understand the onset of pathology in cochlear structure and function. By investigating patients and juvenile Ndp -mutant mice, we elucidated the sequence of onset of physiological changes (in auditory brainstem responses, distorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 55 publications
5
15
1
Order By: Relevance
“…Therefore, the current study is unable to distinguish whether the differential protein expression represents the causative etiology of the disease process. Nonetheless, recent mouse model evidence of SV dysfunction resulting in subsequent delayed SGN dysfunction (72) is supportive of our observations of changes in temporal bones from patients with MD.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the current study is unable to distinguish whether the differential protein expression represents the causative etiology of the disease process. Nonetheless, recent mouse model evidence of SV dysfunction resulting in subsequent delayed SGN dysfunction (72) is supportive of our observations of changes in temporal bones from patients with MD.…”
Section: Discussionsupporting
confidence: 90%
“…Immunostaining for claudin-5 (a component of endothelial cell tight junctions previously reported as a marker of the abnormal vasculature in Norrie disease; Bryant et al, 2022) showed low/absent claudin-5 in most of the Ndp-KO blood vessels of the stria vascularis and spiral ligament compared to WT (Fig 6K -P, white arrows). A few atypical vessels showed high claudin-5 (orange arrows).…”
Section: Effect Of Aav9ndp Treatment On the Lateral Wall Vasculaturementioning
confidence: 82%
“…Gene sets characterising barrier vasculature, BBB1 and 2, BBB endothelial transporters, CNS endothelial and CNS pericyte were significantly positively correlated (FDR < 0.25) with the WT genotype. Dot plot using scRNA seq data of the adult mouse cochlear lateral wall from GEO database: accession numbers GSM5124299, GSM5124300, GSM5124301, and GSM5124302. Gene markers used to distinguish 30 cell type clusters in the UMAP were as previously reported (Gu et al , 2020; Bryant et al , 2022). Dot plot showing expression of the 45 DEGs identified in WT versus Ndp ‐KO analysis in the 30 cell type clusters identified in the adult mouse cochlear lateral wall at the single cell level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations